Learners’ perceptions of a career guidance curriculum in different school-based support systems in Switzerland - Kamm, Chantal [Verfasser]; Gebhardt, Anja [Verfasser]; Gonon, Philipp [Verfasser]; Brühwiler, Christian [Verfasser]; Dernbach-Stolz, Stefanie [Verfasser] (My University, 2021)
“This article examines the different functions and further potential of a curriculum of career guidance in lower secondary school and bridge-year courses. With a focus on young adults following a nonlinear pathway to post-compulsory education in the Swiss Canton of Zurich, we answer the questions why bridge-year courses are attended (RQ1) and how career guidance is perceived (RQ2). Furthermore, optimisation segments for a curriculum of career guidance were analysed from a learner-centred perspective (RQ3). Taking a mixed-method approach, we combine data from a quantitative questionnaire and qualitative problem-centred interviews. To examine differences in attendance of bridge-year courses and the perceived usefulness of supporting actors, quantitative data were analysed by mean ranges. The in-depth qualitative data were analysed using a structured content analysis. The findings underline the importance of an individualised approach to career guidance in both lower secondary school and on bridge-year courses. There is further potential for a curriculum of career guidance in lower secondary school to strengthen the orientation function, taking into account the potential of social structural reproduction. Bridge-year courses should rethink their compensation function given the diversity of their attendees.” (authors’ abstract; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2 Übergänge; P 1.7 Benachteiligte; I 2.2.1 Westeuropa; 370; Berufsorientierung; Allgemeinbildende Schule; Übergangssystem; Benachteiligter Jugendlicher; Lehrplan; Zürich; Schweiz